Proceedings of the 28th Annual ACM Symposium on Applied Computing 2013
DOI: 10.1145/2480362.2480410
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the development of service-oriented robotic systems

Abstract: Robotics has emerged as one of the most prominent research areas in the last years. To cope with the great variety of robots application areas, as well as the heterogeneity of the robots, Service-Oriented Architecture (SOA) has been adopted to develop robotic systems, i.e., the software systems that manage the robots. Nevertheless, there is a lack of studies that provide an updated, fair overview of the development of Service-Oriented Robotic Systems (SORS), i.e., software systems composed by services. The mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 17 publications
(21 reference statements)
0
29
0
Order By: Relevance
“…The process also encompasses the main phases proposed by the consolidated SOMA (Service-Oriented Modeling and Architecture) method [8]. ArchSORS was established based on SORS software architectures available in the literature [5], a set of reference architectures that encompass knowledge of how to structure robotic systems [9], and our expertise on critical embedded systems. Fig.…”
Section: Defining Archsors Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The process also encompasses the main phases proposed by the consolidated SOMA (Service-Oriented Modeling and Architecture) method [8]. ArchSORS was established based on SORS software architectures available in the literature [5], a set of reference architectures that encompass knowledge of how to structure robotic systems [9], and our expertise on critical embedded systems. Fig.…”
Section: Defining Archsors Processmentioning
confidence: 99%
“…Designing robotic systems using SOA allows integration of heterogeneous hardware devices and reuse of complex algorithms, since services are provided through auto-descriptive standard interfaces. Due to its relevance, several works reporting the use of SOA in robotics are available in literature, such as those that we identified in our previous work [5]. Besides that, development environments specially focused on the design of Service-Oriented Robotic Systems (SORS) can be also found [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In a broad, systematic literature review carried out in a previous work [30], we identified 39 studies dedicated to investigate and consolidate the use of SOA in robotics. According to such review, the first attempt to use SOA in robotics was proposed in 2003 by Lee et al [26], which described an architecture for integrating different robots in a multi-robotic application.…”
Section: Software Reuse: From Libraries To Servicesmentioning
confidence: 99%
“…Therefore, we proposed a taxonomy [31], which is a form of classification widely accepted in different domains, such as software architecture [10] and robotics [11]. This taxonomy of services is based on the SORS available in the literature [30], a set of reference architectures of robotics [12], and expertise and knowledge of specialists on how to develop robotic systems. It was evaluated by software architects, software engineers, software developers, and research team leaders from six different institutions of five countries, from both academy and industry.…”
Section: A Taxonomy Of Services For Sorsmentioning
confidence: 99%
See 1 more Smart Citation